2003
DOI: 10.1002/ajhb.10159
|View full text |Cite
|
Sign up to set email alerts
|

Social background and age at menarche in Portuguese university students: A note on the secular changes in Portugal

Abstract: Menarcheal age of a sample of Portuguese university students (n = 3366), born between 1972 and 1983, age 18-23 years, was analyzed. The influence of parents' educational level and occupation, family size, birth order, and degree of urbanization of girl's locality of residence during childhood and adolescence were analyzed as well as secular trend in the Portuguese population. Mean age at menarche for girls born in 1983 was 12.32 years. Parents' educational level and occupation did not show any significant infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
61
3
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 71 publications
10
61
3
1
Order By: Relevance
“…One of the most unexpected findings of this study is that there is no association between number of children in the family and age at menarche in the population studied. This result is contrary to some findings in other populations (Cameron and Nadge, 1996;Padez, 2003), and requires further investigation. In a rural community in Southeast Brazil, Tavares et al (2000) also did not find any difference in age at menarche in relation to number of children in the family, but other studies in Brazil (Riehmer and Violato, 1983;Silva et al, 1982) did find statistically significant relationships between age at menarche and number of children in the family in girls from São Luis (Maranhão state, Northeast Brazil) and Rolândia (Paraná state, South Brazil), with a later age at menarche in girls from larger families.…”
Section: Discussioncontrasting
confidence: 56%
“…One of the most unexpected findings of this study is that there is no association between number of children in the family and age at menarche in the population studied. This result is contrary to some findings in other populations (Cameron and Nadge, 1996;Padez, 2003), and requires further investigation. In a rural community in Southeast Brazil, Tavares et al (2000) also did not find any difference in age at menarche in relation to number of children in the family, but other studies in Brazil (Riehmer and Violato, 1983;Silva et al, 1982) did find statistically significant relationships between age at menarche and number of children in the family in girls from São Luis (Maranhão state, Northeast Brazil) and Rolândia (Paraná state, South Brazil), with a later age at menarche in girls from larger families.…”
Section: Discussioncontrasting
confidence: 56%
“…This conceptual framework basically reflects an evolutionary-biological approach to development and has recently been supported by some animal research showing an influential link between rearing experience and sexual maturation in rats (Cameron et al 2008;Belsky 2012). This may explain a trend toward an earlier pubertal development among girls reared in urban locations where environmental stressors are more prominent than in rural areas, as shown in this study and other research in Western societies (Padez 2003;Dratva et al 2007). However, adolescents at different stages of pubertal timing did not differ in reporting scores on family context, self-esteem, and interpersonal relationships in our study where these measures were assessed concurrently at the pubertal stage.…”
Section: Discussionmentioning
confidence: 66%
“…Secular evolution has led to increased weight and stature during childhood [5,9,15,[17][18][19] and to a downward trend in the mean age at menarche, from about 16 to 13 years, although there have been some differences in various countries [15]. Several studies have now suggested that this trend has been slowing down during the last decade in most industrialized countries [5,15,20], but that it is still ongoing in other countries [7,8,11,21,22]. Moreover, published data have suggested that body weight and nutritional status play a role in the timing of pubertal development [23][24][25][26][27][28][29].…”
mentioning
confidence: 98%